Sārasvata-sandarśanam = Sāraswata-sandaṛśanam : Vāgyogavid-Śrīsarasvatīprasādacaturvedi-krtānām agādhajñānamūlakanibandhānāṃ saṅkalanam - Sarasvatīprasadacaturvedī, 1902- (Pariṣad-granthamālā, 1973)
Articles on the Vedas, Sanskrit grammar and literature, Indic philosophy, etc.